2000
DOI: 10.1038/77305
|View full text |Cite
|
Sign up to set email alerts
|

TnAraOut, A transposon-based approach to identify and characterize essential bacterial genes

Abstract: Identification of genes that encode essential products provides a promising approach to validation of new antibacterial drug targets. We have developed a mariner-based transposon, TnAraOut, that allows efficient identification and characterization of essential genes by transcriptionally fusing them to an outward-facing, arabinose-inducible promoter, PBAD, located at one end of the transposon. In the absence of arabinose, such TnAraOut fusion strains display pronounced growth defects. Of a total of 16 arabinose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
98
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 30 publications
3
98
0
Order By: Relevance
“…The introduction of TnAraOut into V. cholerae and the screen for insertion mutants that are arabinose-dependent for growth were done as described (8) with the following modification. NJ348 was isolated by mating Tn10cm (pBSL181; ref.…”
Section: Methodsmentioning
confidence: 99%
“…The introduction of TnAraOut into V. cholerae and the screen for insertion mutants that are arabinose-dependent for growth were done as described (8) with the following modification. NJ348 was isolated by mating Tn10cm (pBSL181; ref.…”
Section: Methodsmentioning
confidence: 99%
“…The large chromosome encodes the majority of recognizable ''housekeeping'' gene products involved in transcription, translation, metabolism, and cell biology, whereas the small chromosome encodes many more hypothetical gene products. Recently, the V. cholerae genome was scanned genetically for genes encoding ''essential gene products'' defined as those required for optimal growth on rich laboratory media (9). This analysis revealed that the majority of essential genes reside on the large chromosome.…”
mentioning
confidence: 99%
“…Insertions can then be screened on medium that does not turn on the transposon promoter, resulting in loss of viability of those cells that depend on the conditional transposon promoter for growth. This results in the ability to positively identify essential genes and has been used for this purpose (Judson and Mekalanos 2000b). However, the technique is hindered by the fact that few of the transposon inserts within a population will be inserted into gene promoter regions.…”
mentioning
confidence: 99%
“…However, the experimentalist is still faced with the challenge of determining the role of various putative genes. Transposition-based strategies have been developed recently for identifying essential genes (for review, see Judson and Mekalanos 2000a;Hamer et al 2001;Gerdes et al 2002). Conceptually, these methods are based on the fact that transposon insertion into a gene causes loss of gene function (gene knockout), and insertion into an essential gene is lethal to the organism and cannot be observed (Akerley et al 1998;Hare et al 2001).…”
mentioning
confidence: 99%